2012
DOI: 10.3892/or.2012.2109
|View full text |Cite
|
Sign up to set email alerts
|

Live attenuated measles virus vaccine induces apoptosis and promotes tumor regression in lung cancer

Abstract: Abstract. Although the treatment of lung carcinoma has improved, at least 65% of patients with this tumor succumb to progressive disease. Measles virus oncolytic therapy has been reported to be effective in reducing tumor burden in immunocompetent or nude mice; however, its potential to reduce tumor burden in lung carcinoma remains to be determined. Herein, we report the potent antitumor effects of a live attenuated measles vaccine virus Hu-191 strain (MV) against lung carcinoma. Immunocompetent C57BL/6 mice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
1
25
1
Order By: Relevance
“…Our more recent work shows that MV-Edm utilizes mitophagy to promote viral replication by mitigating antiviral innate immune responses [14]. Interestingly, as some apoptotic characteristics have been observed in MV-Edm infected cancer cells reported by several previous studies [15-19], recent work shows that MV-Edm-induced autophagy protects malignant cells from apoptosis [11]. However, how virus-induced autophagy counteracts apoptotic pathways remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our more recent work shows that MV-Edm utilizes mitophagy to promote viral replication by mitigating antiviral innate immune responses [14]. Interestingly, as some apoptotic characteristics have been observed in MV-Edm infected cancer cells reported by several previous studies [15-19], recent work shows that MV-Edm-induced autophagy protects malignant cells from apoptosis [11]. However, how virus-induced autophagy counteracts apoptotic pathways remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism may include transcription of viral genome and virus release which subsequently triggers cellular defense mechanisms causing tumor cell necrosis and apoptosis. Several studies demonstrated the induction of apoptotic tumor cell death following infection with an oncolytic measles virus [23,24,25]. Furthermore, it has been suggested that, depending on the applied virus strain, one potential mechanism of virus-mediated oncolysis may be based on overwhelming budding and release of virions from the infected tumor cell eventually leading to tumor cell lysis [26] (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…(A) Binding to frequently overexpressed virus receptors initiates internalization of the virus into the tumor cell. Viral nucleic acid is released and transcribed which leads to cellular antiviral defense mechanisms such as apoptosis [23,24,25] ( a ). Upon viral gene expression viral proteins are produced exploiting the cellular machinery.…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-1 viral proteins may be used in the development of cancer vaccines for ATL [184,185]. Mouse model studies have reported that a live attenuated measles vaccine virus Hu-191 strain (MV) could effectively suppress the growth of mouse lung carcinoma, suggesting that this approach may be promising in the treatment of human advanced lung cancer [186].…”
Section: Prospects In Cancer Immunotherapymentioning
confidence: 99%